Cable driven robot as a blackboard writer for remote classrooms: modelling, control and trajectory planning. (2016) - Kumar, S. Rakesh; Ramkumar, K.
A remote classroom is one of the successful technologies to share knowledge beyond boundaries and to a large population. But the remote classroom demands for high-end visual systems to display the teachers' writings, which are costly and cannot be afforded by all. This paper presents an alternate idea of using a cable driven robot as a blackboard writer, which is able to replicate the teachers' writing on a blackboard. A planar fully constraint cable driven robot with a writer as an end-effectors is employed as a blackboard writer. It is basically an X-Y plotter that navigates on the planar plane according to the desired trajectory. A novel method for trajectory planning called 'appending trajectory points' was also introduced such that the CDR can faithfully follow the trajectory. The trajectory planner appends trajectory points to decrease the rate change and achieve bumpless transfer in the trajectory. An adaptive PD control scheme was employed for closed loop control to track the trajectory. Finally, the performance of the proposed controller was compared with the conventional PD controller and results are discussed in detail.